1998
DOI: 10.1046/j.1365-2036.1998.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose famotidine and effervescent cimetidine in healthy subjects: a placebo‐controlled overnight pH study

Abstract: Inhibition of gastric acidity over the 12 h post-dose period was significantly greater and endured longer after famotidine 10 mg than after effervescent cimetidine 200 mg, but for the 60 min period immediately after dosing the effect on intragastric pH was significant following effervescent cimetidine 200 mg but not famotidine 10 mg. This suggests effervescent formulations of H2-receptor antagonists with an acid buffer have a more rapid effect on intragastric pH than film-coated tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The E max model provided the drug exposure that produced half the maximum effect (EC 50 ), as follows: %Time at pH >4 over 24 hours = E max × AUC /(EC 50 + AUC ). Secondary efficacy endpoints included: %Time at pH >4 during the daytime or night‐time; the mean intragastric pH over 24 hours; the area under the effect curve (AUEC; i.e., area under the intragastric pH vs time curve), measured at 15 minutes intervals from 0 to 2 hours after dosing; and Day 1 to Day 7 ratio of the %Time at pH >4 over 24 hours . Dose‐proportionality in the PK parameters was determined with a linear regression analysis of the log‐transformed AUC inf versus the log‐transformed dose (power model).…”
Section: Methodsmentioning
confidence: 99%
“…The E max model provided the drug exposure that produced half the maximum effect (EC 50 ), as follows: %Time at pH >4 over 24 hours = E max × AUC /(EC 50 + AUC ). Secondary efficacy endpoints included: %Time at pH >4 during the daytime or night‐time; the mean intragastric pH over 24 hours; the area under the effect curve (AUEC; i.e., area under the intragastric pH vs time curve), measured at 15 minutes intervals from 0 to 2 hours after dosing; and Day 1 to Day 7 ratio of the %Time at pH >4 over 24 hours . Dose‐proportionality in the PK parameters was determined with a linear regression analysis of the log‐transformed AUC inf versus the log‐transformed dose (power model).…”
Section: Methodsmentioning
confidence: 99%
“…When pantoprazole was compared with a drug that produces significantly less acid suppression by a different mechanism (cimetidine), the increased mortality was seen only with the PPI, not with the H-2 blocker. Cimetidine has a rapid onset of action but a short half-life, with detectable changes a pH noted for only up to eight hours after oral administration (Reilly et al 1998). Pantoprazole irreversibly binds to the proton pump and therefore alters pH for much longer than its plasma half-life (Shin and Sachs 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have, however, demonstrated that at over‐the‐counter doses, cimetidine has a slightly lower antisecretory efficacy than famotidine and ranitidine 9 , . 11 On the other hand, a new effervescent preparation of 200 mg cimetidine has been shown to induce a more rapid suppressive effect on intragastric acidity than film‐coated tablets of famotidine 31 . This is likely to induce a more rapid symptom relief during the daytime.…”
Section: Discussionmentioning
confidence: 99%